MODEL DISEMINASI INFORMASI GEOSPASIAL PULAU-PULAU KECIL TERLUAR BERBASIS PEMANFAATAN PENGINDERAAN JAUH DAN GOOGLE MAPPING SYSTEM - Sarno, Sarno (Institut Teknologi Sepuluh Nopember, 2013)
This paper describes the implementation of Geospatial Information and Communication Technology (ICT-Geospatial) in the dissemination of geospatial information of outermost small islands in Indonesia. Dissemination models allow the user via the Internet and web media to easily interact and acquire geospatial information of outermost small islands that are needed through a web browser online. This study is a follow-up development of remote sensing applications of geospatial information